The apothecary diaries. 4 - Hyūga, Natsu (Apothecary diaries., 2025)
Outside of her official duties, Maomao helps friends and acquaintances in the rear palace. Xiaolan needs a new job after her term of service ends, and Consort Lishu is convinced she's seen a ghost! Then, when complications arise with Gyokuyou's pregnancy, Maomao realizes her skills are inadequate to handle the life-threatening situation. Although Maomao knows someone who can help, they haven't been welcome in the rear palace for a very long time... Maomao also begins to connect the dots between seemingly unrelated incidents in the rear palace. Will knowing too much put her life in danger?